2007
DOI: 10.1007/s00508-007-0777-4
|View full text |Cite
|
Sign up to set email alerts
|

Family medicine practice and research: Survey of physicians' attitudes towards scientific research in a post-communist transition country

Abstract: Family medicine practitioners in a transition country have a more positive attitude towards science than towards alternative medicine, despite the adverse situation in which they practice. To involve family medicine practitioners in research, interventions must be directed towards changes in behavior and practice and not only towards increasing positive attitudes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…While the majority of participants of elective CAM courses in our study held positive views about science, too, agreement to the two statements was significantly lower than among participants in the control group. Croatian surveys among students and doctors also found a negative correlation between attitudes towards CAM and science [18, 22]. However, the ratings on our beyond science scale suggest that even many control group students share the view that a purely biomedical scientific approach alone might not be sufficient.…”
Section: Discussionmentioning
confidence: 94%
“…While the majority of participants of elective CAM courses in our study held positive views about science, too, agreement to the two statements was significantly lower than among participants in the control group. Croatian surveys among students and doctors also found a negative correlation between attitudes towards CAM and science [18, 22]. However, the ratings on our beyond science scale suggest that even many control group students share the view that a purely biomedical scientific approach alone might not be sufficient.…”
Section: Discussionmentioning
confidence: 94%
“…In Croatia, primary health care has a long tradition and represents patients' gateway to the health care system (21). A recent study showed that family medicine practitioners in the context of intensive socioeconomic transitions in Croatia had positive attitude toward scientific research in medicine (22). However, positive attitudes do not suffice for real engagement of family physicians in teaching and research (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported a progressively larger fraction of medical students and graduates who expressed serious interest in research careers [6]. Our research group showed that teaching research methodology is associated with increase in positive attitudes towards science among medical students [8], and that among family medicine practitioners there was a positive association between attitude toward science and opinion of research methodology training as a mandatory part of the medical curriculum [9].…”
Section: Introductionmentioning
confidence: 48%